Brazilian Propolis Effects on Growth, Productivity Performance, Gut Characteristics and Physiological Changes in Broiler Chickens - Mahmoud , U.T.; Amen, O.A.; Applegate, T.J.; Cheng, H.W. (International Journal of Poultry Science, 2017)
Objective: This study aimed to examine the effect of dietary Brazilian propolis on the growth performance, physiological homeostasis and gut characteristics in broiler chickens reared under mild chronic heat stress. Materials and Methods: Five hundred and four 15 days old male broiler chicks were fed one of six diet (0.0, 100, 250, 500, 1000 and 3000 mg kg–1 propolis). Growth performance was evaluated in terms of Body Weight (BW), Body Weight Gain (BWG), Feed Intake (FI) and Feed Conversion Ratio (FCR) at 2 weeks intervals to 42 day of age. At 42 day of age 12 birds from each group were randomly selected and sacrificed for determination of the relative weight of internal organs and cecal contents were collected for microbial enumeration. Duodenal, jejunal and ileal tissue samples were collected for measuring villus height and width, crypt depth and villus crypt ratio. Also, blood was collected for subpopulations of leukocytes counts and serum chemical and hormonal analysis. In addition, brain samples were collected for determination of the heat stress-induced changes of the Heat Shock Protein 70 (HSP70) gene expression. The data were analyzed by one-way analysis of variance using the General Linear Models (GLM) procedure. Results: The results indicated that dietary propolis supplementation had no effect on growth performance and liver, heart, gizzard and spleen weights (p>0.05). While, compared to controls, the abdominal fat weight was increased with propolis supplementation (p = 0.035). Propolis did not affect cecal concentrations of Escherichia coli, total coliforms, Enterococcus spp. and total lactobacilli (p>0.05). However, compared to controls, the Bifidobacterium spp., population was lower in birds fed diet with propolis at 1000 mg kg–1 (p = 0.005). Propolis had no effect (p>0.05) on intestinal villus height and width, crypt depth and villus:crypt ratio. Compared to controls, propolis dietary supplementation did not affect the populations of eosinophils, monocytes and basophils; and serum concentrations of total proteins, globulins, phosphate, calcium, glucose and thyroid hormones as well as HSP70 mRNA expression in brain tissues (p>0.05, respectively). However, propolis regardless of dose reduced the number of heterophils, heterophil:lymphocyte ratio (H/L) and serum corticosterone and aminotransferase (AST) concentrations (p